2020
DOI: 10.1097/sih.0000000000000529
|View full text |Cite
|
Sign up to set email alerts
|

Use of Simulation to Measure the Effects of Just-in-Time Information to Prevent Nursing Medication Errors

Abstract: Introduction: Medication administration error (MAE) is the improper dispensing of medication. It is a significant contributor to the occurrence of medical errors. A novel systems thinking approach using a pediatric simulation and student nurses were used to evaluate the benefit of applying just-in-time information (JITI) to reduce medication errors. Just-intime information applies highly focused information delivered when needed. Methods: A smart device app was developed to provide JITI medication administrati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(10 citation statements)
references
References 18 publications
0
8
0
Order By: Relevance
“…The most frequent simulations are performed in high-fidelity laboratories (58%), using mannequins, labels, equipment and an environment prepared to get as close as possible to real care (Minor et al, 2019;Lane;Roberts, 2021;Kothari et al, 2021;O' Leary et al, 2013;Damhoff et al, 2014;Hayes et al, 2015;Keating et al, 2021;Raurell-Torredà et al, 2021;Russ et al, 2014;Hawley et al, 2019;Dudas;Barone, 2015;Stevens et al, 2015;Wyatt et al, 2020;Siebert et al, 2021;Adapa et al, 2012;booth et al, 2018;Breitkreuz et al, 2016;Estock et al, 2018;Enriquez et al, 2017;Prakash et al, 2014;Pinkney et al, 2014;VYAS et al, 2012;MERRY et al, 2017;GARCIA et al 2017;Metzger et al, 2015;Khan et al, 2016;Cooke et al, 2017;Pinkney et al, 2019;Frenzel et al, 2020;Hebbar et al, 2018;Cotteret et al, 2019;Porter et al, 2014;Wang et al, 2017;Booth et al, 2017;Lobos et al, 2019;Thibault et al, 2019;Crimmins et al, 2018;Berg et al, 2021).…”
Section: Resultsmentioning
confidence: 99%
“…The most frequent simulations are performed in high-fidelity laboratories (58%), using mannequins, labels, equipment and an environment prepared to get as close as possible to real care (Minor et al, 2019;Lane;Roberts, 2021;Kothari et al, 2021;O' Leary et al, 2013;Damhoff et al, 2014;Hayes et al, 2015;Keating et al, 2021;Raurell-Torredà et al, 2021;Russ et al, 2014;Hawley et al, 2019;Dudas;Barone, 2015;Stevens et al, 2015;Wyatt et al, 2020;Siebert et al, 2021;Adapa et al, 2012;booth et al, 2018;Breitkreuz et al, 2016;Estock et al, 2018;Enriquez et al, 2017;Prakash et al, 2014;Pinkney et al, 2014;VYAS et al, 2012;MERRY et al, 2017;GARCIA et al 2017;Metzger et al, 2015;Khan et al, 2016;Cooke et al, 2017;Pinkney et al, 2019;Frenzel et al, 2020;Hebbar et al, 2018;Cotteret et al, 2019;Porter et al, 2014;Wang et al, 2017;Booth et al, 2017;Lobos et al, 2019;Thibault et al, 2019;Crimmins et al, 2018;Berg et al, 2021).…”
Section: Resultsmentioning
confidence: 99%
“…Previous studies have reported successful training outcomes using Just-In-Time training for skill refresh to perform a procedure resulting in improved procedural confidence, performance, patient satisfaction, and clinical outcomes [6,[9][10][11][12]. A recent study suggests the use of Just-In-Time training improved HCPs' competencies (knowledge) to respond during the COVID-19 pandemic [13].…”
Section: Discussionmentioning
confidence: 99%
“…We used the basic principles of Just-in-Time training to develop this novel delivery method that is JITOT [6]. Educators and curriculum developers may find some of the following tips helpful in setting up JITOT: Our training evaluation indicated that more than 90% of the respondents (n=29) either agreed or strongly agreed regarding the value of the training content to their job, received new information, clarified their current information, used appropriate delivery method of the training, and will use the concepts they learned at their job.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations